Analisis Kesulitan Siswa Kelas V Sekolah Dasar dalam Menyelesaikan Soal Cerita pada Materi Bangun Ruang - Unaenah, Een; Elyipuspita, Melina; Salsabila, Nada; Safitri, Sela (MASALIQ, 2023)
Mathematics is an important lesson that has a role in human life. This lesson continues from the elementary school level to university, formal education cannot be separated from teaching mathematics. One of the materials in mathematics in elementary school is about geometric shapes which are analyzed to provide phenomena regarding the problems that students will face in their lives. Introducing problems as stories to provide insight to students. have options to solve a problem. This research was carried out in order to analyze what challenges or difficulties were experienced by fifth grade elementary school students when trying to solve story problems based on geometrical material. This requires knowledge of the factors that contribute to student difficulties, and solutions to the problem must be sought. This study uses a descriptive qualitative approach. This exam was guided by 4 out of 5 students at SD Tangerang. This study collected data using a purposive testing method, namely by selecting subjects who had received material about building spaces. Seeing the consequences of the text test above, it tends to be suspected that the challenges experienced by grade 5 elementary school students in solving story problems about building space material are difficulties in describing the state of geometric nets, understanding, and solving problem-based questions, calculating integers and division.